Answers

The Brainliest Answer!
2014-10-16T09:15:30+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
         y = x² + 3 x

New axes are X and Y.

Shift right,            X = x + 3

Stretch vertically by a factor of 6 :  Y = 6y

Reflected across x-axis :      Y becomes  -Y       =>    Y = -6y

Graph shifted 8 units upwards :  Y becomes Y+8    =>  Y = -6y+8

So,  x = X-3  and  y = (8-Y)/6

Substitute this in the original equation for the graph:

(8-Y)/6 = (X-3)² + 3 (X-3) = (X-3)(X-3+3) = X² - 3X

8 - Y = 6 X² - 18 X
       Y = 8 - 6 X² + 18 X             or     Y = -6 (X - 3/2)² + 43/2

So  equation of the graph:  y = 8 - 6 x² + 18 x    or  -6 (x - 3/2)² + 43/2

2 5 2
i hope that is easy enough to understand
click on thank you link
thanx n u r welcom